Functional Improvement of Regulatory T Cells from Rheumatoid Arthritis Subjects Induced by Capsular Polysaccharide Glucuronoxylomannogalactan - Pericolini, Eva (Public Library of Science, 2014)
OBJECTIVE: Regulatory T cells (Treg) play a critical role in the prevention of autoimmunity, and the suppressive activity of these cells is impaired in rheumatoid arthritis (RA). The aim of the present study was to investigate function and properties of Treg of RA patients in response to purified polysaccharide glucuronoxylomannogalactan (GXMGal). METHODS: Flow cytometry and western blot analysis were used to investigate the frequency, function and properties of Treg cells. RESULTS: GXMGal was able to: i) induce strong increase of FOXP3 on CD4(+) T cells without affecting the number of CD4(+)CD25(+)FOXP3(+) Treg cells with parallel increase in the percentage of non-conventional CD4(+)CD25(−)FOXP3(+) Treg cells; ii) increase intracellular levels of TGF-β1 in CD4(+)CD25(−)FOXP3(+) Treg cells and of IL-10 in both CD4(+)CD25(+)FOXP3(+) and CD4(+)CD25(−)FOXP3(+) Treg cells; iii) enhance the suppressive activity of CD4(+)CD25(+)FOXP3(+) and CD4(+)CD25(−)FOXP3(+) Treg cells in terms of inhibition of effector T cell activity and increased secretion of IL-10; iv) decrease Th1 response as demonstrated by inhibition of T-bet activation and down-regulation of IFN-γ and IL-12p70 production; v) decrease Th17 differentiation by down-regulating pSTAT3 activation and IL-17A, IL-23, IL-21, IL-22 and IL-6 production. CONCLUSION: These data show that GXMGal improves Treg functions and increases the number and function of CD4(+)CD25(−)FOXP3(+) Treg cells of RA patients. It is suggested that GXMGal may be potentially useful for restoring impaired Treg functions in autoimmune disorders and for developing Treg cell-based strategies for the treatment of these diseases.